Lillianite homologues from Kutna Hora ore district, Czech Republic: a case of large-scale Sb for Bi substitution - Pazout,R. (Journal of Geosciences, 2017)
Numerous complex Pb-Bi-Sb-Ag sulphosalt minerals belonging to the lillianite homologous series previously unknown in Czech Republic, including a new mineral species, have been identified in samples from hydrothermal vein mineralization of the Kutna Hora Ag-Pb-Zn ore district, central Bohemia, Czech Republic. Identified lillianite homologues include both Bi members (minerals of the lillianite branch) and Sb members (andorite branch) and show an extensive Sb for Bi substitution. Nine distinct compositional groups were identified among Bi members, corresponding to: N = 4 (gustavite, terrywallaceite, staroceskeite - recently approved IMA No. 2016-101), N = 5.5 (vikingite), N = 6 (treasurite), N = 7 (eskimoite and (Ag, Bi)-rich heyrovskyite), N = 8 (erzwiesite) and schirmerite (Type 2). Single-crystal XRD measurement of Bi members with N = 4 revealed a new mineral, staroceskeite. Unlike gustavite and terrywallaceite, which are monoclinic, staroceskeite is orthorhombic with a = 4.2539(8), b = 13.3094(8), c = 19.625(1) Å, and the ideal formula is Ag0.70Pb1.60(Bi1.35Sb1.35)Σ2.70S6, corresponding to Nchem = 4, Bi/(Bi + Sb) = 0.50 and substitution percentage L% = 70. Among Sb members, minerals with N = 4 (andorite series) and N = 5.0-5.5 were found. Relations between substitution percentage, chemical N and Sb content have been observed. The description of the new occurrence of Bi sulphosalts, including Sb-rich varieties and a continuous transition from Bi-dominant to Sb-dominant phases with N = 4 provides new information on compositional limits in natural sulphosalts. Comparable range of the Bi3+ ↔ Sb3+substitution in lillianite homologues with N = 4 has not been observed before.
Keywords: bismuth lillianite homologues; andorite series; chemistry; powder and single-crystal X-ray diffraction; Kutna Hora; Czech Republic